Medical Adhesives: Bioinspired Nanoparticulate Medical Glues for Minimally Invasive Tissue Repair (Adv. Healthcare Mater. 16/2015). Issue 16 (November 2015) - Lee, Yuhan; Xu, Chenjie; Sebastin, Monisha; Lee, Albert; Holwell, Nathan; Xu, Calvin; Miranda Nieves, David; Mu, Luye; Langer, Robert S.; Lin, Charles; Karp, Jeffrey M.
Abstract : Methods to deliver viscous medical glues to the tissues through small incisions or with small channels are critical for minimally invasive surgeries. Inspired by the granule‐packaged glue delivery system of sandcastle worms, J. M. Karp and co‐workers show on page 2587 nanoparticulate formulation of viscous hydrophobic light‐activated adhesive based on poly(glycerol sebacate)‐acrylate.